Identifying potential drivers of distribution patterns of invasive Corbicula fluminea relative to native freshwater mussels (Unionidae) across spatial scales. Issue 3 (18th March 2022) - Kelley, Taylor E.; Hopper, Garrett W.; Sánchez González, Irene; Bucholz, Jamie R.; Atkinson, Carla L.
Abstract: This study aimed to identify the importance of ecological factors to distribution patterns of the invasive Clam ( Corbicula fluminea ) relative to native mussels (family: Unionidae) across seven rivers within the Mobile and Tennessee basins, Southeast United States. We quantitatively surveyed dense, diverse native mussel aggregations across 20 river reaches and estimated mussel density, biomass, and species richness along with density of invasive C . fluminea (hereafter Corbicula ). We measured substrate particle size, velocity, and depth in quadrats where animals were collected. Additionally, we characterized reach scale environmental parameters including seston quantity and quality (% Carbon, % Nitrogen, % Phosphorous), water chemistry (ammonium [ NH 4 + ], soluble reactive phosphorous [SRP]), and watershed area and land cover. Using model selection, logistic regression, and multivariate analysis, we characterized habitat features and their association to invasive Corbicula within mussel beds. We found that Corbicula were more likely to occur and more abundant in quadrats with greater mussel biomass, larger substrate size, faster water velocity, and shallower water depth. At the reach scale, Corbicula densities increased where particle sizes were larger. Mussel richness, density, and biomass increased with watershed area. Water column NH 4 + increased at reaches with more urban land cover. No land cover variables influenced Corbicula populations or mussel communities. The strong overlapping distribution of Corbicula and mussels support the hypothesis that Corbicula are not necessarily limited by habitat factors and may be passengers of change in rivers where mussels have declined due to habitat degradation. Whether Corbicula is facilitated by mussels or negatively interacts with mussels in these systems remains to be seen. Focused experiments that manipulate patch scale variables would improve our understanding of the role of species interactions (e.g., competition, predation, facilitation) or physical habitat factors in influencing spatial overlap between Corbicula and native mussels. Abstract : Identifying environmental factors associated with the distribution of invasive species relative to native species is fundamental to conservation and management. Our quantitative surveys of dense, diverse native mussel beds in rivers across a broad geographic area showed that invasive Corbicula fluminea were more likely to occur and more abundant where mussels are. The strong positive association between invasive and native bivalves support the hypothesis that C . fluminea are not necessarily limited by habitat factors and may be passengers of change in rivers where mussels have declined due to habitat degradation.